Implementation of Automatic Control System of Coal Preparation Plant - HAN Chao-hui (Gong-kuang zidonghua, 2011)
The paper introduced composition and detailed design of automatic control system of coal preparation plant, described implementation of key functions of the system. The actual application showed that the system realizes automatic control of all links of coal preparation plant, which is safe, reliable and has strong expandability.